Mathematical modeling of compact anisotropic relativistic fluid spheres in higher spacetime dimensions. (11th August 2016) - Sen, Banashree; Grammenos, Theophanes; Bhar, Piyali; Rahaman, Farook
Abstract : Completing previous work, a new class of interior solutions for compact static fluid spheres exhibiting pressure anisotropy, admitting conformal motion, and having 7, 8, 9, and 10 spacetime dimensions, respectively, is presented. Einstein's field equations without cosmological constant are solved for a particular energy density distribution function, assuming non‐commutative geometry of spacetime. The behavior of the physical quantities obtained does not exclude the possible existence of ultra‐compact, though rather exotic, stars in higher spacetime dimensions. Copyright © 2016 John Wiley & Sons, Ltd.